Clinical application value of simultaneous plasma and bronchoalveolar lavage fluid metagenomic next generation sequencing in patients with pneumonia-derived sepsis - Jiayan Li; Dongxu Pan; Yuxin Guo; Bo Zhang; Xinglin Lu; Chen Deng; Feifei Xu; Zongnan Lv; Qinhe Chen; Yafeng Zheng; Shuhao Nong; Lihua Su; et al. (BMC Infectious Diseases)
Abstract Background Despite the increasing use of metagenomic next-generation sequencing (mNGS) in sepsis, identifying clinically relevant pathogens remains challenging. This study was aimed to evaluate the clinical utility of simultaneous plasma and bronchoalveolar lavage fluid (BALF) detection using mNGS. Methods This retrospective study enrolled 95 patients with pneumonia-derived sepsis (PDS) admitted to the intensive care unit (ICU) between October 2021 and January 2023. Patients were divided into two groups: mNGS group (n = 60) and the non-mNGS group (n = 35), based on whether simultaneous plasma and BALF mNGS were conducted. All patients underwent conventional microbiological tests (CMT), including bacterial/fungal culture of peripheral blood and BALF, as well as sputum culture, detection of 1, 3-beta-D- glucan in BALF and RT-PCR testing. The clinical data of the enrolled patients were collected, and the detection performance and prognosis of plasma mNGS, BALF mNGS and CMT were compared. Results The mNGS group exhibited a lower mortality rate than the non-mNGS group (35.0% vs. 57.1%, P = 0.034). Simultaneous detection in dual-sample resulted in a higher proportion of microorganisms identified as definite causes of sepsis alert compared to detection in either plasma or BALF alone (55.6% vs. 20.8% vs. 18.8%, P<0.001). Acinetobacter baumannii, Stenotrophomonas maltophilia, Candida albicans, and human mastadenovirus B were the primary strains responsible for infections in PDS patients. Patients with lower white blood cells and neutrophil indices had a greater consistency in dual-sample mNGS. Patients in the mNGS group had more antibiotic adjustments compared to the non-mNGS group (85.71% vs. 33.33%, P<0.001). The percentage of neutrophils was a risk factor for mortality in PDS patients (P = 0.002). Conclusion Dual sample mNGS has the advantage of detecting and determining the pathogenicity of more pathogens and has the potential to improve the prognosis of patients with PDS.